1999
DOI: 10.1002/(sici)1521-4141(199902)29:02<530::aid-immu530>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

C-X-C and C-C chemokine expression and secretion by the human colonic epithelial cell line, HT-29: differential effect of T lymphocyte-derived cytokines

Abstract: Differential chemokine production by colonic epithelial cells is thought to contribute to the characteristic increased infiltration of selected population of leukocytes cells in inflammatory bowel disease. We have previously demonstrated that IL-13 enhances IL-1alpha-induced IL-8 secretion by the colonic epithelial cell line HT-29. We have now explored the C-C chemokine expression and modulation in this system. The combination of TNF-alpha and IFN-gamma was the minimal stimulation required for regulated on act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 29 publications
2
26
0
2
Order By: Relevance
“…CCR5 binds the CC chemokines macrophage-inflammatory protein (MIP)-1␣, MIP-1␤, and RANTES (20), which are released from intestinal epithelial cells upon exposure to inflammatory mediators (21,22). Expression of both MIP-1␣ and RANTES is increased in the intestinal mucosa in IBD (23)(24)(25).…”
mentioning
confidence: 44%
“…CCR5 binds the CC chemokines macrophage-inflammatory protein (MIP)-1␣, MIP-1␤, and RANTES (20), which are released from intestinal epithelial cells upon exposure to inflammatory mediators (21,22). Expression of both MIP-1␣ and RANTES is increased in the intestinal mucosa in IBD (23)(24)(25).…”
mentioning
confidence: 44%
“…IFN-γ or TNF-α induces differential up-regulation of CXC and CC chemokine secretions in colonic epithelial cell lines (23,31). In this study, the stimulation with C. difficile toxin A did not up-regulate IFN-γ expression in HT-29 and Caco-2 intestinal epithelial cells.…”
Section: Ifn-γ and Tnf-α Increase The Basolateral Release Of CC Chemomentioning
confidence: 99%
“…granulocyte/macrophage-colony stimulating factor and granulocyte-colony stimulating factor) expression by activated monocytes/macrophages or endothelial cells (1,6). Another target of IL-13 is epithelial cells and we have recently demonstrated that IL-13 can modulate chemokine generation from the human colonic epithelial cell line HT-29 (7,8) and inhibit iNOS expression and NO generation in this system (9). Activation of the signaling enzyme phosphatidylinositol 3-kinase (PI 3-kinase) by IL-13 is important for mediating these effects (8,10).…”
Section: Interleukin-13 (Il-13)mentioning
confidence: 99%
“…Another target of IL-13 is epithelial cells and we have recently demonstrated that IL-13 can modulate chemokine generation from the human colonic epithelial cell line HT-29 (7,8) and inhibit iNOS expression and NO generation in this system (9). Activation of the signaling enzyme phosphatidylinositol 3-kinase (PI 3-kinase) by IL-13 is important for mediating these effects (8,10). PI 3-kinase and its major downstream effector, the serine/threonine kinase protein kinase B (PKB), have been shown to be key mediators of growth factor-induced cell survival and protection against c-Myc-induced cell death in fibroblasts (11)(12)(13).…”
Section: Interleukin-13 (Il-13)mentioning
confidence: 99%
See 1 more Smart Citation